Development of Tri Hita Karana-Oriented Flipbooks For Science Literacy in Grade III Elementary School - Desak Putu Yulia Kusumayanti; I Gede Suwindia; I Nyoman Raka (Jurnal Pendidikan Dasar dan Keguruan, 2026)
In order to enhance third-grade students' scientific literacy during science classes, this project aims to develop and assess flipbook resources based on Tri Hita Karana. This research and development (R&D) project employed the ADDIE paradigm, which consists of phases for analysis, design, development, implementation, and evaluation. Third-grade instructors, 39 kids from Cluster V in the Busungbiu District, media specialists, language specialists, and material specialists made up the research subjects. Data was gathered using science literacy assessments, teacher response questionnaires, and validation sheets. For both qualitative and quantitative analysis, Lawshe's validity test (CVR and CVI), practicality percentage analysis, one-sample t-test, and effect size computation were employed. The study found that the flipbook medium was deemed genuine with a CVI score of 0.90 for the material aspect, 0.67 for language, and 0.56 for presentation. Additionally, with a 96.43% proportion, this media was deemed extremely practical and useful in enhancing scientific literacy, with an impact size of 1.314 and a significant value of 0.000 (highly effective category). Consequently, Tri Hita Karana-focused flipbooks might be utilized as a cutting-edge scientific teaching aid in primary school settings.